Pro Open Source Mail: Building an Enterprise Mail Solution - Smith, Curtis (Apress, 2012)
Something as ubiquitous as e-mail can be taken for granted so easily. You may curse it, but as soon as “the server goes down,” you can’t stop from trying to check your e-mail twice as often until it is available again. Every Linux distribution comes with a mail server application. Perhaps you’re already running a small e-mail system for your home network, personal domain, or a larger organization, but you want to take that service a notch or two or three higher.